2018
DOI: 10.1038/s41598-018-27008-w
|View full text |Cite
|
Sign up to set email alerts
|

Effect of HIV-1 Tat on the formation of the mitotic spindle by interaction with ribosomal protein S3

Abstract: Human immunodeficiency virus type 1 (HIV-1) Tat, an important regulator of viral transcription, interacts with diverse cellular proteins and promotes or inhibits cell proliferation. Here, we show that ribosomal protein S3 (RPS3) plays an important role in mitosis through an interaction with α-tubulin and that Tat binds to and inhibits the localization of RPS3 in the mitotic spindle during mitosis. RPS3 colocalized with α-tubulin around chromosomes in the mitotic spindle. Depletion of RPS3 promoted α-tubulin as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…1A). Numerous research groups have demonstrated that these RPs may be utilized by diverse viruses for efficient viral infection (25,30,(37)(38)(39)(40)(41)(42)(43)(44). Notably, the candidate protein RPL13, a member of the L13E family, is conserved in a wide range of species, including plants, yeast, and animals (45,46).…”
Section: Resultsmentioning
confidence: 99%
“…1A). Numerous research groups have demonstrated that these RPs may be utilized by diverse viruses for efficient viral infection (25,30,(37)(38)(39)(40)(41)(42)(43)(44). Notably, the candidate protein RPL13, a member of the L13E family, is conserved in a wide range of species, including plants, yeast, and animals (45,46).…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that RPS3 plays an important role in cell mitosis by interacting with α-tubulin. When cells are infected with HIV-1, HIV-1 Tat protein can interact with RPS3 and disturb its localization on the spindle, and ultimately inhibit cell proliferation [18]. Moreover, the function of RPS3 depends on its own nuclear translocation, which is regulated by protein kinases such as SRC [19].…”
Section: Regulation Network After Infectionmentioning
confidence: 99%
“…As regards alphaviruses, RPSA includes different binding sites for Venezualian equine encephalitis virus (VEEV) and Sindbis virus (SINV) (Jamieson et al 2008 ; Malygin et al 2009 ). HIV-1 Tat inhibits cell proliferation via an interaction with RPS3 and increases the level of RPS3 in the nucleus, thereby disrupting mitotic spindle formation during HIV-1 infection (Kim and Kim 2018 ). FMDV VP1 inhibits the antiviral response of RPSA by interacting with RPSA to promote FMDV replication (Zhu et al 2019 ).…”
Section: Alterations In Functional Characteristics Of Rps For Viral Tmentioning
confidence: 99%